Kedudukan dan Proses Legislasi Qanun Aceh dalam Sistem Hukum Nasional - Denisa, Elsa; Azzahra, Annisa Futri; Achtia, Alika Chairana; Sabila, Muhammad Ilham; Najmudin, Deden (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Aceh's Qanun, as a legal product of Special Autonomy under Law No. 11/2006, occupies a unique and paradoxical position within Indonesia's national legal framework. Formally, it is hierarchically equivalent to a Provincial Regulation (Perda), yet its substantive authority transcends the limits of ordinary regional autonomy, venturing into domains traditionally reserved for uniform national law—most prominently with the establishment of Islamic criminal law through Qanun Jinayat. This creates a systemic legal dualism where citizens, particularly Muslims, are subject to two concurrent criminal regimes: the national Criminal Code (KUHP) and the Jinayat provisions. Its legislative process reflects this complexity, functioning as a multi-level political arena involving intense negotiations among the Aceh DPRD, the Governor, the Aceh Sharia Court (for syariah-based Qanuns), and the Central Government via the Ministry of Home Affairs' evaluation. This ex-ante control mechanism often prioritizes political and administrative considerations over deep juridical review. While Qanun Jinayat attracts significant scholarly and public attention for its controversial nature, the majority of Qanuns actually govern more technical, secular fields like spatial planning and public services. These face different but equally critical challenges, including regulatory overlaps and weak drafting quality, highlighting a gap between the symbolic prominence of syariah and the practical needs of governance. A fundamental flaw in the system is the weak ex-post control; mechanisms for judicial review are unclear and systematic evaluations of a Qanun's implementation and impact are virtually absent. Consequently, many Qanuns exist and are enforced in a state of persistent legal uncertainty, undermining the very rule of law and equal protection that the legal system aims to guarantee, ultimately posing a continuous challenge to national legal integration